The Implication of Excessive Internet Usage on the Study of Hadith - & Nur Saadah bt Hamisan Khair, Ismail bin Abdullah (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
The internet allows its users to access information with a click of button. It is a powerful source of vast information on almost every subject and issue, contributing to promotion of knowledge especially in academic matters. The use of multitudes of websites has both positive and negative impacts on the users’ minds. Excessive use of the internet has become almost habit of most of the users. It is where the negative impact makes its way. The Prophet Muhammad (s.a.w.) encouraged Muslims to be moderate in most of their actions and avoid excessiveness. As per this prophetic tradition, the use of the internet should be controlled in all the fields of knowledge, specifically in the study of the Prophetic traditions (hadith) which preserve the sum and substance of the utterances, deeds, directives, and descriptive anecdotes connected with the life of the Prophet Muhammad (s.a.w.) and his Companions. hadith literature constitutes a source of Islamic thought, law, and life only next to the Qur’an. This paper intends to analyze one of the challenges posed to the students of hadith by the modern technology of the internet.